Engaging Pediatric Health Professionals in Interactive Online Ethics Education - Plantz, Diane M. (The Hastings Center report, 2014)
Bioethical decision-making in pediatrics diverges from similar decisions in other medical domains because the young child is not an autonomous decision-maker, while the teen is developing—and should be encouraged to develop—autonomy and decisional capacity. Thus the balance between autonomy and beneficence is fundamentally different in pediatrics than in adult medicine. While ethical dilemmas that reflect these fundamental issues are common, many pediatric physician and nursing training programs do not delve into the issues or offer specific training about how to deal with borderline cases. To meet this need, the Children's Mercy Bioethics Center in Kansas City, Missouri, created a program specifically dedicated to serving practicing, experienced pediatric health professionals. Our students come from various professional disciplines: they are doctors, nurses, social workers, chaplains, lawyers, psychologists, counselors, and hospital administrators practicing in pediatrics.